RESEARCH ON THE PERFORMANCE IMPACT OF MARKETING EXPENDITURE FROM THE PERSPECTIVE OF DIFFERENTIATION STRATEGY IN PHARMACEUTICAL ENTERPRISES - Qian, Zhang (МІЖНАРОДНА ЕКОНОМІКА В УМОВАХ КЛІМАТИЧНИХ ЗМІН: ГЛОБАЛЬНІ ВИКЛИКИ, 2026)
.